A renal angiomyolipoma with extension to the renal vein and asymptomatic fat pulmonary embolus. (August 2014) - Harris, Kassem; Hatem, Elie; Maroun, Rabih; Seminara, Donna; Maniatis, Theodore
Renal angiomyolipoma (AML) is a rare benign tumor that can extend into the renal vein, inferior vena cava and the right atrium. AML is a mesenchymal tumor composed of smooth muscle, fat and vascular elements. In rare instances, the tumor may release a fatty tissue to the pulmonary vasculature, which can lead to cardiopulmonary collapse and death. Only four cases of fat pulmonary embolism secondary to AML have been reported in the literature but our case was the first to present as asymptomatic. Our patient had left renal AML extending to the renal vein that was associated with fat pulmonary embolus. The patient underwent uncomplicated radical nephrectomy and was discharged home on no anticoagulation. Follow-up chest computed tomography showed no extension of the pulmonary embolism. Whether embolectomy or anticoagulation is necessary in asymptomatic pulmonary embolism secondary to renal AML is unclear. Although controversial, some surgeons prefer to place an inferior vena cava filter prior to radical nephrectomy to prevent dislodgement of new intraoperative emboli, which can lead to catastrophic outcome.